Vigilance for carcinoid heart disease is still required in the era of somatostatin analogues: Lessons from a case series. Issue 3 (14th April 2021) - Chan, David L.; Pavlakis, Nick; Crumbaker, Megan; Lawrence, Ben; Barber, Camilla; Price, Timothy J.; Michael, Michael; Oberg, Kjell
Abstract: Aim: Carcinoid heart disease (CHD) is a well‐documented complication of neuroendocrine tumors (NETs) due to secreted hormones causing fibrosis. Somatostatin analogues (SSAs) can decrease hormonal secretion and inhibit tumor growth. The reported incidence of CHD has decreased as SSA use has increased. We describe a series of patients who have developed CHD even though they were treated with SSA therapy. Methods: Nine patients were seen in four centers in Australia and New Zealand. The average duration of follow‐up from diagnosis was 39 months. Results: Three patients had Grade 1 and six Grade 2 disease by World Health Organization 2010 criteria. All patients had no CHD symptoms at baseline and started SSA therapy soon after diagnosis, yet developed significant, symptomatic cardiac dysfunction in their disease course. The median time from NET diagnosis to SSA initiation was 1 month, and median time from NET diagnosis to CHD diagnosis was 23 months (range 4–52). All patients who were tested had persistently increased hormonal levels (chromogranin A, urinary 5‐hydroxyindolacetic acid). Conclusions: The good symptomatic control afforded by SSAs should not lead to reduced vigilance in screening for CHD, especially in patients with persistently elevated hormonal assays. Clinicians should consider regular echocardiographic screening in patients with a secretory syndrome. Abstract : Carcinoid heart disease may develop in patients with neuroendocrine tumours even if symptoms are well controlled on somatostatin analogues.